Refinity smart compact - W Ismail, Wan Nur Fatimah Ayuni; Ismail, Siti Hajar; Rozlan, Muhammad Irfan; Mohd Akhir, Noor Erni Fazlina (Faculty Of Chemical Engineering, 2025)
The Refinity Smart Compact represents a pioneering innovation combining user-friendly features, contemporary design, and eco-friendliness. Featuring an integrated smart sensor and a digital percentage display, it effectively tackles essential consumer concerns like the sudden depletion of powder. The robust, recyclable matte plastic guarantees durability while appealing to environmentally aware customers, making Refinity practical and sustainable. These characteristics position the product as a compelling option in the beauty accessories sector that caters to the rising demand for intelligent and green tools. This product holds significant potential for enhancement and adaptation as it progresses with technological developments. Future versions monitoring or more advanced connectivity features, such as app compatibility for automatic refill monitoring, or offer customization possibilities to accommodate various user preferences. These upgrades would allow Refinity to maintain a competitive advantage in a rapidly changing market while effectively meeting consumer demands. The innovation of Refinity is well-prepared for a successful market introduction. Its innovative design, which emphasizes sustainability and the incorporation of modern technology, differentiates it from conventional beauty compacts. By successfully combining functionality and visual appeal and constantly adapting to technological progress, Refinity positions itself as a forward-looking product that can hold its own in an increasingly competitive landscape.